Whole body vibration as an adjunct to static stretching - Feland, J. B.; Hawks, M.; Hopkins, J. T.; Hunter, I.; Johnson, A. W.; Eggett, D. L. (International Journal of Sports Medicine, 2010)
This study was a randomized control trial. The purpose of this study was twofold: 1) to determine if stretching the hamstrings during whole-body-vibration (WBV) is more effective than static stretching alone; and 2) to monitor retention of flexibility changes. The main outcome measure was hamstring flexibility as measured in degrees using a passive knee extension test. Thirty-four recreationally active college-age subjects (23.4±1.7 yrs) completed this study (22 males, 12 females, avg. ht.=175.6±6.4 cm, avg. wt.=74.9±11.8 kg). Subjects were assigned to a control group (C), a static stretch group (SS), or a vibration + static stretch group (V). Subjects stretched 5 days/wk for 4-weeks and were followed for 3-weeks after cessation to monitor retention. Analysis showed a significant difference between treatment groups (p<0.0001), time (p<0.0001), gender (p=0.0002) and in treatment*time (p=0.0119), with 14%±3.86% (SEM) and 22%±3.86% (SEM) increases in flexibility after 4-weeks of stretching for the SS and V groups respectively. Three-week follow-up showed SS returning to baseline with V group still 6.4 degrees (11%±3.88% (SEM)) more flexible than at baseline. Stretching concurrently with vibration on a WBV platform appears to be a good adjunct to static stretching with the potential to enhance retention of flexibility gains.